Similarities and Differences Between COVID-19-Related Multisystem Inflammatory Syndrome in Children and Kawasaki Disease - Lee, Min-Sheng; Liu, Yi-Ching; Tsai, Ching-Chung; Hsu, Jong-Hau; Wu, Jiunn-Ren (Frontiers in Pediatrics, 2021)
In December 2019, the coronavirus COVID-19 was first reported in Wuhan, China. The mortality rate in adults was around 1-5%, and only a small proportion of children requires hospitalization and intensive care. Recently, an increasing COVID-19 cases associated with a new multisystem inflammatory syndrome. The clinical features and laboratory examinations are like those of Kawasaki disease (KD), KD shock syndrome, and toxic shock syndrome. But the new disorder has somewhat distinct clinical features and laboratory characteristics. This condition, also known as “pediatric multisystem inflammatory syndrome temporally associated with SARS-CoV-2 (PIMS-TS)” or “multisystem inflammatory syndrome in children (MIS-C) associated with COVID-19”, has been mainly noticed in Europe and the United State. This emerging phenomenon raised the issue whether this cluster is KD triggered by SARS-CoV-2 or a syndrome characterized by multisystem inflammation that mimics KD. The narrative review is to discuss the differences between the PIMS-TS/MIS-C and KD, and to alert pediatricians to this new and aggressive phenotype in children.